# Bessel polynomials

In mathematics, the Bessel polynomials are an orthogonal sequence of polynomials. There are a number of different but closely related definitions. The definition favored by mathematicians is given by the series[1]: 101

${\displaystyle y_{n}(x)=\sum _{k=0}^{n}{\frac {(n+k)!}{(n-k)!k!}}\,\left({\frac {x}{2}}\right)^{k}.}$

Another definition, favored by electrical engineers, is sometimes known as the reverse Bessel polynomials[2]: 8 [3]: 15

${\displaystyle \theta _{n}(x)=x^{n}\,y_{n}(1/x)=\sum _{k=0}^{n}{\frac {(n+k)!}{(n-k)!k!}}\,{\frac {x^{n-k}}{2^{k}}}.}$

The coefficients of the second definition are the same as the first but in reverse order. For example, the third-degree Bessel polynomial is

${\displaystyle y_{3}(x)=15x^{3}+15x^{2}+6x+1}$

while the third-degree reverse Bessel polynomial is

${\displaystyle \theta _{3}(x)=x^{3}+6x^{2}+15x+15.}$

The reverse Bessel polynomial is used in the design of Bessel electronic filters.

## Properties

### Definition in terms of Bessel functions

The Bessel polynomial may also be defined using Bessel functions from which the polynomial draws its name.

${\displaystyle y_{n}(x)=\,x^{n}\theta _{n}(1/x)\,}$
${\displaystyle y_{n}(x)={\sqrt {\frac {2}{\pi x}}}\,e^{1/x}K_{n+{\frac {1}{2}}}(1/x)}$
${\displaystyle \theta _{n}(x)={\sqrt {\frac {2}{\pi }}}\,x^{n+1/2}e^{x}K_{n+{\frac {1}{2}}}(x)}$

where Kn(x) is a modified Bessel function of the second kind, yn(x) is the ordinary polynomial, and θn(x) is the reverse polynomial .[2]: 7, 34  For example:[4]

${\displaystyle y_{3}(x)=15x^{3}+15x^{2}+6x+1={\sqrt {\frac {2}{\pi x}}}\,e^{1/x}K_{3+{\frac {1}{2}}}(1/x)}$

### Definition as a hypergeometric function

The Bessel polynomial may also be defined as a confluent hypergeometric function[5]: 8

${\displaystyle y_{n}(x)=\,_{2}F_{0}(-n,n+1;;-x/2)=\left({\frac {2}{x}}\right)^{-n}U\left(-n,-2n,{\frac {2}{x}}\right)=\left({\frac {2}{x}}\right)^{n+1}U\left(n+1,2n+2,{\frac {2}{x}}\right).}$

A similar expression holds true for the generalized Bessel polynomials (see below):[2]: 35

${\displaystyle y_{n}(x;a,b)=\,_{2}F_{0}(-n,n+a-1;;-x/b)=\left({\frac {b}{x}}\right)^{n+a-1}U\left(n+a-1,2n+a,{\frac {b}{x}}\right).}$

The reverse Bessel polynomial may be defined as a generalized Laguerre polynomial:

${\displaystyle \theta _{n}(x)={\frac {n!}{(-2)^{n}}}\,L_{n}^{-2n-1}(2x)}$

from which it follows that it may also be defined as a hypergeometric function:

${\displaystyle \theta _{n}(x)={\frac {(-2n)_{n}}{(-2)^{n}}}\,\,_{1}F_{1}(-n;-2n;2x)}$

where (−2n)n is the Pochhammer symbol (rising factorial).

### Generating function

The Bessel polynomials, with index shifted, have the generating function

${\displaystyle \sum _{n=0}^{\infty }{\sqrt {\frac {2}{\pi }}}x^{n+{\frac {1}{2}}}e^{x}K_{n-{\frac {1}{2}}}(x){\frac {t^{n}}{n!}}=1+x\sum _{n=1}^{\infty }\theta _{n-1}(x){\frac {t^{n}}{n!}}=e^{x(1-{\sqrt {1-2t}})}.}$

Differentiating with respect to ${\displaystyle t}$, cancelling ${\displaystyle x}$, yields the generating function for the polynomials ${\displaystyle \{\theta _{n}\}_{n\geq 0}}$

${\displaystyle \sum _{n=0}^{\infty }\theta _{n}(x){\frac {t^{n}}{n!}}={\frac {1}{\sqrt {1-2t}}}e^{x(1-{\sqrt {1-2t}})}.}$

Similar generating function exists for the ${\displaystyle y_{n}}$ polynomials as well:[1]: 106

${\displaystyle \sum _{n=0}^{\infty }y_{n-1}(x){\frac {t^{n}}{n!}}=\exp \left({\frac {1-{\sqrt {1-2xt}}}{x}}\right).}$

Upon setting ${\displaystyle t=z-xz^{2}/2}$, one has the following representation for the exponential function:[1]: 107

${\displaystyle e^{z}=\sum _{n=0}^{\infty }y_{n-1}(x){\frac {(z-xz^{2}/2)^{n}}{n!}}.}$

### Recursion

The Bessel polynomial may also be defined by a recursion formula:

${\displaystyle y_{0}(x)=1\,}$
${\displaystyle y_{1}(x)=x+1\,}$
${\displaystyle y_{n}(x)=(2n\!-\!1)x\,y_{n-1}(x)+y_{n-2}(x)\,}$

and

${\displaystyle \theta _{0}(x)=1\,}$
${\displaystyle \theta _{1}(x)=x+1\,}$
${\displaystyle \theta _{n}(x)=(2n\!-\!1)\theta _{n-1}(x)+x^{2}\theta _{n-2}(x)\,}$

### Differential equation

The Bessel polynomial obeys the following differential equation:

${\displaystyle x^{2}{\frac {d^{2}y_{n}(x)}{dx^{2}}}+2(x\!+\!1){\frac {dy_{n}(x)}{dx}}-n(n+1)y_{n}(x)=0}$

and

${\displaystyle x{\frac {d^{2}\theta _{n}(x)}{dx^{2}}}-2(x\!+\!n){\frac {d\theta _{n}(x)}{dx}}+2n\,\theta _{n}(x)=0}$

### Orthogonality

The Bessel polynomials are orthogonal with respect to the weight ${\displaystyle e^{-2/x}}$ integrated over the unit circle of the complex plane.[1]: 104  In other words, if ${\displaystyle n\neq m}$,

${\displaystyle \int _{0}^{2\pi }y_{n}\left(e^{i\theta }\right)y_{m}\left(e^{i\theta }\right)ie^{i\theta }\mathrm {d} \theta =0}$

## Generalization

### Explicit form

A generalization of the Bessel polynomials have been suggested in literature, as following:

${\displaystyle y_{n}(x;\alpha ,\beta ):=(-1)^{n}n!\left({\frac {x}{\beta }}\right)^{n}L_{n}^{(-1-2n-\alpha )}\left({\frac {\beta }{x}}\right),}$

the corresponding reverse polynomials are

${\displaystyle \theta _{n}(x;\alpha ,\beta ):={\frac {n!}{(-\beta )^{n}}}L_{n}^{(-1-2n-\alpha )}(\beta x)=x^{n}y_{n}\left({\frac {1}{x}};\alpha ,\beta \right).}$

The explicit coefficients of the ${\displaystyle y_{n}(x;\alpha ,\beta )}$ polynomials are:[1]: 108

${\displaystyle y_{n}(x;\alpha ,\beta )=\sum _{k=0}^{n}{\binom {n}{k}}(n+k+\alpha -2)^{\underline {k}}\left({\frac {x}{\beta }}\right)^{k}.}$

Consequently, the ${\displaystyle \theta _{n}(x;\alpha ,\beta )}$ polynomials can explicitly be written as follows:

${\displaystyle \theta _{n}(x;\alpha ,\beta )=\sum _{k=0}^{n}{\binom {n}{k}}(2n-k+\alpha -2)^{\underline {n-k}}{\frac {x^{k}}{\beta ^{n-k}}}.}$

For the weighting function

${\displaystyle \rho (x;\alpha ,\beta ):={}_{1}F_{1}\left(1,\alpha -1,-{\frac {\beta }{x}}\right)}$

they are orthogonal, for the relation

${\displaystyle 0=\oint _{c}\rho (x;\alpha ,\beta )y_{n}(x;\alpha ,\beta )y_{m}(x;\alpha ,\beta )\,\mathrm {d} x}$

holds for mn and c a curve surrounding the 0 point.

They specialize to the Bessel polynomials for α = β = 2, in which situation ρ(x) = exp(−2/x).

### Rodrigues formula for Bessel polynomials

The Rodrigues formula for the Bessel polynomials as particular solutions of the above differential equation is :

${\displaystyle B_{n}^{(\alpha ,\beta )}(x)={\frac {a_{n}^{(\alpha ,\beta )}}{x^{\alpha }e^{-{\frac {\beta }{x}}}}}\left({\frac {d}{dx}}\right)^{n}(x^{\alpha +2n}e^{-{\frac {\beta }{x}}})}$

where a(α, β)
n
are normalization coefficients.

### Associated Bessel polynomials

According to this generalization we have the following generalized differential equation for associated Bessel polynomials:

${\displaystyle x^{2}{\frac {d^{2}B_{n,m}^{(\alpha ,\beta )}(x)}{dx^{2}}}+[(\alpha +2)x+\beta ]{\frac {dB_{n,m}^{(\alpha ,\beta )}(x)}{dx}}-\left[n(\alpha +n+1)+{\frac {m\beta }{x}}\right]B_{n,m}^{(\alpha ,\beta )}(x)=0}$

where ${\displaystyle 0\leq m\leq n}$. The solutions are,

${\displaystyle B_{n,m}^{(\alpha ,\beta )}(x)={\frac {a_{n,m}^{(\alpha ,\beta )}}{x^{\alpha +m}e^{-{\frac {\beta }{x}}}}}\left({\frac {d}{dx}}\right)^{n-m}(x^{\alpha +2n}e^{-{\frac {\beta }{x}}})}$

## Zeros

If one denotes the zeros of ${\displaystyle y_{n}(x;\alpha ,\beta )}$ as ${\displaystyle \alpha _{k}^{(n)}(\alpha ,\beta )}$, and that of the ${\displaystyle \theta _{n}(x;\alpha ,\beta )}$ by ${\displaystyle \beta _{k}^{(n)}(\alpha ,\beta )}$, then the following estimates exist:[2]: 82

${\displaystyle {\frac {2}{n(n+\alpha -1)}}\leq \alpha _{k}^{(n)}(\alpha ,2)\leq {\frac {2}{n+\alpha -1}},}$

and

${\displaystyle {\frac {n+\alpha -1}{2}}\leq \beta _{k}^{(n)}(\alpha ,2)\leq {\frac {n(n+\alpha -1)}{2}},}$

for all ${\displaystyle \alpha \geq 2}$. Moreover, all these zeros have negative real part.

Sharper results can be said if one resorts to more powerful theorems regarding the estimates of zeros of polynomials (more concretely, the Parabola Theorem of Saff and Varga, or differential equations techniques).[2]: 88 [6] One result is the following:[7]

${\displaystyle {\frac {2}{2n+\alpha -{\frac {2}{3}}}}\leq \alpha _{k}^{(n)}(\alpha ,2)\leq {\frac {2}{n+\alpha -1}}.}$

## Particular values

The Bessel polynomials ${\displaystyle y_{n}(x)}$ up to ${\displaystyle n=5}$ are[8]

{\displaystyle {\begin{aligned}y_{0}(x)&=1\\y_{1}(x)&=x+1\\y_{2}(x)&=3x^{2}+3x+1\\y_{3}(x)&=15x^{3}+15x^{2}+6x+1\\y_{4}(x)&=105x^{4}+105x^{3}+45x^{2}+10x+1\\y_{5}(x)&=945x^{5}+945x^{4}+420x^{3}+105x^{2}+15x+1\end{aligned}}}

No Bessel polynomial can be factored into lower degree polynomials with rational coefficients.[9] The reverse Bessel polynomials are obtained by reversing the coefficients. Equivalently, ${\textstyle \theta _{k}(x)=x^{k}y_{k}(1/x)}$. This results in the following:

{\displaystyle {\begin{aligned}\theta _{0}(x)&=1\\\theta _{1}(x)&=x+1\\\theta _{2}(x)&=x^{2}+3x+3\\\theta _{3}(x)&=x^{3}+6x^{2}+15x+15\\\theta _{4}(x)&=x^{4}+10x^{3}+45x^{2}+105x+105\\\theta _{5}(x)&=x^{5}+15x^{4}+105x^{3}+420x^{2}+945x+945\\\end{aligned}}}